Seasonal and Spatial Variation in Biodiversity of Campus Wetlands - Rhiannon Bostian (UNC Test Journal, 2025)
My project aimed to identify the species of aquatic vertebrates, especially anurans and salamanders, and macroinvertebrates that inhabit wetlands on the UNC Asheville campus. Many of the wetlands on campus are ephemeral ponds, but two ponds stay wet year-round. My goal was to quantify the species present and compare diversity between ephemeral and permanent ponds. Differences in amphibian diversity were expected, as many amphibian species will not breed in permanent ponds because they contain fish predators. Hurricane Helene impacted campus soon after I began sampling, providing an opportunity to compare diversity before and after this major event. From September 2024 into April 2025, campus ponds were sampled using sweep nets and bucket traps. I recorded the abundance of amphibians and fish and the presence/absence of various macroinvertebrate taxa. Notes about the conditions of the ponds were also recorded, such as fullness and presence of ice that either prevented full sampling or influenced the individuals present. The bucket traps used in the survey yielded two different salamander species, Ambystoma maculatum and A. talpoideum, as well as tadpoles of several anuran species. Sweep netting revealed the presence of nematodes, snails, and daphnia, as well as damselfly, mayfly, and dragonfly larvae. Surprisingly, there were salamanders present in ponds that contained sunfish. The results of this study provided a foundation that can serve as a baseline to track changes in pond diversity through time as campus land use patterns change